Genomic imprinting - Bartolomei, Marisa (Henry Stewart Talks, 2011)
Genomic Imprinting: Definition of genomic imprinting, Why genomic imprinting is essential for development, Imprinted genes, Mechanism of genomic imprinting, H19/Igf2 imprinted locus, Marking of imprinted genes in the germline, Maintenance of genomic imprints